Modeling the particle capture performance by vertically aligned carbon nanotubes for a comet rendezvous sample return. Issue 7 (1st April 2022) - Serizawa, Ryota; Yano, Hajime; Takeda, Yuki; Oizumi, Shuto; Ishibashi, Yukihiro; Arai, Kazuyoshi; Li, Yuexuan; Hirahara, Kaori; Hirai, Takayuki; Sun, Yuchen; Kooi, Steven E.; Nelson, Keith A.
Abstract: Capturing and analyzing cometary coma dust lead to elucidate the origin of water and organics within the Solar System. For future sample return missions of fragile organic microparticles from a cometary nucleus, rendezvous operations will become more favorable than flyby missions because the comet rendezvous can reduce impacting velocity of cometary dust particles slow enough to capture them intact, rather than hypervelocity flyby sampling like the Stardust mission to the Comet Wild 2. At JAXA/ISAS, we are developing a core technology for sample return of microparticles ejected at as a lower velocity as an order of 0.1 m/s to 100 m/s after rendezvous with a cometary nucleus. We have devised "Vertically Aligned Carbon Nanotube (VA-CNT)" carpets as an effective capture medium for such a purpose. The VA-CNT carpets can amplify van der Waals force with impacting particles due to the large contact area and can capture intact the microparticles of sub-mm in size or smaller in the vacuum space environment while preserving its adhesive strength. In this study, we modelled capturing mechanism of microparticles on the VA-CNT carpets by the impact analysis software "LS-DYNA" to further improve its particle capture performance. The stress–strain constitutive laws for the VA-CNT carpets were derived via indentation and inputted to our simulations that were consistent with impact experiment results. The simulations reveal that the mechanical property of the VA-CNT carpets is the key for the improvement of its particle capture performance suitable for sampling the cometary dust.